Synthesis and characterization of GaN/quartz nanostructure using pulsed laser ablation in liquid. (1st November 2022) - Fakhri, Makram A; Alwahib, Ali A; Salim, Evan T; Abdul Amir, Husam Aldin A; Alsultany, Forat H; Hashim, U
Abstract: The pulsed laser ablation in liquid approach was used to synthesize gallium nitride (GaN) nanoparticles (NPs) at six distinct ablation energies. GaN target with purity of 99.999% submerged in 5 ml ethanol of 99.99% purty and fired with a Nd:YAG pulsed laser. The nanoparticle was deposited on a quartz substrate using the drop cast technique. Two peaks of h-GaN nanostructures are detected in the XRD pattern, at 2 θ = 34.64 and 37.98, reflected from the (002) and (100) planes, respectively. The hexagonal crystal nature of GaN is indicated by the structural features, which is shown in the XRD pattern. The greatest laser power, 2000 mJ, shows a modest emission peaking at 3.34 eV, according to photoluminescence (PL) spectra. At 1400 mJ, the highest emission peak was 3.83 eV. The pulsed laser is used in this study to create nanoparticles with various characteristics.